CARA PANDANG HIDUP SEBAGAI UPAYA PENINGKATAN PERTUMBUHAN EKONOMI MELALUI PENYULUHAN DALAM PERENCANAAN KEUANGAN - Andres Dharma Nurhalim (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This community service activity is motivated by the lack of understanding and ability of the community in preparing financial management. Many people are still reluctant to do financial planning on the grounds that they do not understand the guidelines for preparing financial management. This is what underlies the need to carry out this service activity with the aim of helping the community in preparing financial management so that later the community can manage finances. The dedication activity was carried out in April 2022 at the Indralokamonastery in Tangerang. The method used is divided into two stages in the form of delivery of material and assistance to people who wish to develop financial management. With this community service activity, it can provide new knowledge concepts for the community so that they can prepare financial planning that has been carried out.